Bioproduction of Enantiopure (R)‐ and (S)‐2‐Phenylglycinols from Styrenes and Renewable Feedstocks. Issue 7 (21st December 2020) - Sekar, Balaji Sundara; Mao, Jiwei; Lukito, Benedict Ryan; Wang, Zilong; Li, Zhi
Abstract: Enantiopure ( R )‐ and ( S )‐2‐phenylglycinols are important chiral building blocks for pharmaceutical manufacturing. Several chemical and enzymatic methods for their synthesis were reported, either involving multi‐step synthesis or starting from a relatively complex chemical. Here, we developed one‐pot simple syntheses of enantiopure ( R )‐ and ( S )‐2‐phenylglycinols from cheap starting materials and renewable feedstocks. Enzyme cascades consisting of epoxidation‐hydrolysis‐oxidation‐transamination were developed to convert styrene 2  a to ( R )‐ and ( S )‐2‐phenylglycinol 1  a, with butanediol dehydrogenase for alcohol oxidation as well as BmTA and NfTA for ( R )‐ and ( S )‐enantioselective transamination, respectively. The engineered E. coli strains expressing the cascades produced 1015 mg/L ( R )‐1  a in >99% ee and 315 mg/L ( S )‐1  a in 91% ee, respectively, from styrene 2  a . The same cascade also converted substituted styrenes 2  b –k and indene 2  l into substituted ( R )‐phenylglycinols 1  b –k and (1 R, 2 R )‐1‐amino‐2‐indanol 1  l in 95–>99% ee . To transform bio‐based L ‐phenylalanine 6 to ( R )‐1  a and ( S )‐1  a, ( R )‐ and ( S )‐enantioselective enzyme cascades for deamination‐decarboxylation‐epoxidation‐hydrolysis‐oxidation‐transamination were developed. The engineered E. coli strains produced ( R )‐1  a and ( S )‐1  a in high ee at 576 mg/L and 356 mg/L, respectively, from L ‐phenylalanine 6, as the first synthesis of these compounds from a bio‐based chemical. Finally, L ‐phenylalanine biosynthesis pathway was combined with ( R )‐ or ( S )‐enantioselective cascade in one strain or coupled strains, to achieve the first synthesis of ( R )‐1  a and ( S )‐1  a from a renewable feedstock. The coupled strain approach enhanced the production, affording 274 and 384 mg/L ( R )‐1  a and 274 and 301 mg/L ( S )‐1  a, from glucose and glycerol, respectively. The developed methods could be potentially useful to produce these high‐value chemicals from cheap starting materials and renewable feedstocks in a green and sustainable manner. Abstract :